M−O Bonding Beyond the Oxo Wall: Spectroscopy and Reactivity of Cobalt(III)‐Oxyl and Cobalt(III)‐Oxo Complexes. Issue 28 (11th June 2019) - Andris, Erik; Navrátil, Rafael; Jašík, Juraj; Srnec, Martin; Rodríguez, Mònica; Costas, Miquel; Roithová, Jana
Abstract: Terminal oxo complexes of late transition metals are frequently proposed reactive intermediates. However, they are scarcely known beyond Group 8. Using mass spectrometry, we prepared and characterized two such complexes: [(N4Py)Co III (O)] + (1 ) and [(N4Py)Co IV (O)] 2+ (2 ). Infrared photodissociation spectroscopy revealed that the Co−O bond in 1 is rather strong, in accordance with its lack of chemical reactivity. On the contrary, 2 has a very weak Co−O bond characterized by a stretching frequency of ≤659 cm −1 . Accordingly, 2 can abstract hydrogen atoms from non‐activated secondary alkanes. Previously, this reactivity has only been observed in the gas phase for small, coordinatively unsaturated metal complexes. Multireference ab‐initio calculations suggest that 2, formally a cobalt(IV)‐oxo complex, is best described as cobalt(III)‐oxyl. Our results provide important data on changes to metal‐oxo bonding behind the oxo wall and show that cobalt‐oxo complexes are promising targets for developing highly active C−H oxidation catalysts. Abstract : Tear down this oxo wall ! Behind the oxo wall, metal‐oxo complexes become unstable or highly reactive because antibonding M−O orbitals are being filled and the bond order drops below two. As an example, [(N4Py)Co(O)] 2+ abstracts hydrogen from cyclohexane in a barrierless reaction in the gas phase. Adding an electron, however, does not weaken but strengthen the Co−O bond in the reduced [(N4Py)Co(O)] + complex.